Comorbidities and clinical severity of COVID-19: systematic review and meta-analysis - Thais María Plasencia-Urizarri; Raúl Aguilera-Rodríguez; Luis Enrique Almaguer Mederos (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: The recent emergence of COVID-19 has become a serious global health problem. The identification of comorbidities associated with the clinical severity in COVID-19 patients is of paramount significance for the appropriate therapeutic approach of affected patients. Objective: To evaluate the risk of severe clinical presentation of COVID-19 in patients with comorbidities. Materials and methods: A systematic literature search and meta-analysis was conducted in specialized databases to obtain information from articles published until March 20, 2020. All relevant papers with information on the association between clinical severity and comorbidities were included. The odds ratio with 95 % confidence interval and fixed or random effect models were used.  Results: Thirteen studies were included for a total of 99 817 patients. Global effects were obtained for hypertension (OR: 4.05; 95 % CI: 3.45-4.74), cardiovascular disease (OR: 4.39; 95 % CI: 3.29-5.87), diabetes mellitus (OR: 3.53; 95 % CI: 2.79-4.47), smoking (OR: 2.87; 95 % CI: 1.81-4.54), chronic lung disease (OR: 2.73; 95 % CI: 2.55-2.94), chronic kidney disease (OR: 5.60; 95 % CI: 4.13-7.60), chronic liver disease (OR: 1.98; 95 % CI: 1.08-3.64), and immunodeficiency (OR: 2.90; 95 % CI: 2.06-4.09) in severe patients compared with non-severe patients. Conclusions: Chronic kidney disease, cardiovascular disease, hypertension and diabetes are among the comorbidities with the highest risk of severe clinical presentation in COVID-19 patients, followed in importance by immunodeficiency, smoking, chronic lung disease and chronic liver disease.